2015
DOI: 10.1097/rmr.0000000000000057
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Hip

Abstract: Hip pain is common in all age groups, and osteoarthritis of this joint is an increasingly recognized problem particularly in aging populations. One of the primary goals in the diagnostic evaluation in patients with hip pain is to identify and correct pathologies that could progress to osteoarthritis. Magnetic resonance imaging (MRI) has become an important noninvasive method for characterizing hip anatomy and pathology in these patients. Improvements in MRI hardware and techniques have allowed high spatial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 114 publications
(116 reference statements)
0
9
0
1
Order By: Relevance
“…While not mainstream in clinical imaging yet, these techniques will likely become more important in the future, particularly in evaluation of athletes. Such techniques include delayed gadolinium-enhanced MR imaging of cartilage, T2 cartilage mapping, and T1 mapping, which are directed toward identification of early molecular defects secondary to glycosaminoglycan depletion, free water content, and proteoglycan loss, respectively, before cartilage abnormalities become evident with conventional MR imaging sequences (62,84,85).…”
Section: Articular Cartilagementioning
confidence: 99%
“…While not mainstream in clinical imaging yet, these techniques will likely become more important in the future, particularly in evaluation of athletes. Such techniques include delayed gadolinium-enhanced MR imaging of cartilage, T2 cartilage mapping, and T1 mapping, which are directed toward identification of early molecular defects secondary to glycosaminoglycan depletion, free water content, and proteoglycan loss, respectively, before cartilage abnormalities become evident with conventional MR imaging sequences (62,84,85).…”
Section: Articular Cartilagementioning
confidence: 99%
“…When characterizing hip anatomy and pathology, MRI can also identify synovial proliferations, joint effusion, articular cartilage abnormalities, ligaments, subchondral bone, muscles, and juxtaarticular soft tissue [4]. MRI facilitates the accurate identification, localization, and characterization of hip illness, hence aiding the diagnosis and therapy of a variety of hip pathological conditions [5]. The purpose of this study was to investigate the role of MRI in the diagnosis of non-traumatic hip joint discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…T2 relaxation times can be used to measure cartilage degeneration due to their dependency on the water and collagen content of the extracellular matrix as well as orientation of collagen fibers (2). T2 mapping has been used in multiple clinical studies mostly in the knee (2-7), hip (4,8,9) and spine (10)(11)(12)(13)(14)(15)(16), many of which demonstrated that T2 mapping was able to identify early cartilage degeneration.…”
Section: Introductionmentioning
confidence: 99%